EXTRACURRICULAR ACTIVITIES AND THEIR TYPES IN HIGH SCHOOLS - Dehqonova, Ohista; Taylanov, Nizom (Физико-технологического образование, 2022)
In this work we consider the problem of extracurricular activities and their types - it is the creation of the necessary conditions for the socialization of the child’s personality by the teacher through the organization of various extracurricular activities for schoolchildren. Main goal is to correct the gaps in the knowledge and skills acquired by students in computer science in a timely manner, to achieve quality and efficiency of education